(untitled) (Revista Direitos Humanos e Democracia, 2026)
This research addresses the phenomenon of migration and the human right to education. The general objective is to analyze the contributions of school mediation to the realization of the human right to education for migrant children and adolescents. The specific objectives are: 1) To address the (non-)access to the human right to education by migrant children and adolescents in the Brazilian context; 2) To present the contributions of school mediation as a mechanism for the realization of human rights and the treatment of conflicts in the school environment involving migrants. The theoretical basis used to support the discussion is Eligio Resta’s Theory of Fraternal Law and Luis Alberto Warat’s perspectives on transformative mediation. Methodologically, the research employs the hypothetical-deductive method, guided by bibliographic and documentary analysis. Given the intersection between migration and education produced by the Theory of Fraternal Law, the following question arises: What are the contributions of school mediation to the realization of the human right to education for migrant children and adolescents in Brazil? From a community and popular perspective, school mediation takes on its transformative dimension when it stimulates the construction of shared common spaces, based on non-violent communication, a culture of peace, compassionate language, dialogue, and understanding, in order to realize the human right to education for migrant children and adolescents in Brazil.